Book Reviews (Journal of Finance, 1994)
Investment Mathematics and Statistics . By ANDREW ADAMS, DELLA BLOOMFIELD, PHILIP BOOTH, and PETER ENGLAND Portfolio Management: New Models for Successful Investment Decisions . By C. KENNETH JONES Corporate Liquidity: Management and Measurement . By JARL G. KALL‐BERG and KENNETH L. PARKINSON Stock Index Futures: Theories and International Evidence . By CHARLES M. S. SUTCLIFFE